Differentiating Grammar Instruction for Advanced ESL Learners (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the importance and methodology of differentiated grammar instruction for advanced learners of English as a Second Language (ESL). While advanced learners typically demonstrate mastery of fundamental grammar rules, they often face challenges with complex structures, subtle usage, and stylistic accuracy. Differentiated instruction allows teachers to cater to individual learner needs, varying backgrounds, and language goals through flexible grouping, personalized tasks, and targeted feedback. Drawing on principles from second language acquisition theory and learner-centered pedagogy, this article outlines effective strategies and tools for tailoring grammar instruction in advanced ESL classrooms to optimize engagement, accuracy, and fluency.